Literature review about Neo4j graph database as a feasible alternative for replacing RDBMS - Santos López, Félix Melchor (2015)
Neo4 is a NoSQL graph database that has been emerging in the fields of social networks and web applications with high concurrency. The characteristics of supporting technological transactions and a high scalability have been attracting the attention of the academic world. Therefore, this literature review focuses in analyse four research papers developed in USA, Spain, India and Germany. The authors show the results of benchmarking between Neo4j and other models, including relational databases. The aim of this paper is to illustrate the features of Neo4j, the architecture and advantages. Also, the purpose is to identify if Neo4 is a reliable alternative for replacing the RDBMS (Relational Database Management System) and offer suggestions for carrying out better experiments.